A case study of the characteristics of jumping responsible for different training effects in volleyball players - Okano, K.; Kuki, S.; Akiyama, N.; Tanigawa, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
This study focused on volleyball spike jump performance. We classified players based on different types of jumping ability and tested the effects of strength training and plyometrics for each type of ability. Players who excelled in their ability to acquire greater impulse (countermovement jump or CMJ type) showed no significant changes in spike jump height with strength training (improvement in maximum muscle strength), but demonstrated a significant improvement in jump height after plyometrics. In contrast, players with outstanding execution of ballistic movement (rebound jump or RJ type) showed a significant improvement in their spike jump height with strength training (an improvement in maximum muscle strength), but a significant loss of jump height after plyometrics. This reveals that the same training program results in players jumping lower or higher, depending on the jump type. When formulating training to improve the jump height of volleyball players, these results suggest that the type of training must be selected based on the individual player`s jumping ability.